A prospective multicenter phase II study evaluating multimodality treatment of patients with peritoneal carcinomatosis arising from appendiceal and colorectal cancer: the COMBATAC trial - Glockzin, Gabriel; Rochon, Justine; Arnold, Dirk; Lang, Sven A.; Klebl, Frank; Zeman, Florian; Koller, Michael; Schlitt, Hans J.; Piso, Pompiliu (BMC cancer, 2013)
Peritoneal carcinomatosis is regarded as a common sign of advanced tumor stage, tumor progression or local recurrence of appendiceal and colorectal cancer and is generally associated with poor prognosis. Although survival of patients with advanced stage CRC has markedly improved over the last 20 years with systemic treatment, comprising combination chemotherapy +/− monoclonal antibodies, the oncological outcome—especially of the subgroup of patients with peritoneal metastases—is still unsatisfactory. In addition to systemic therapy, cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) are specific treatment options for a selected group of these patients and may provide an additional therapeutic benefit in the framework of an interdisciplinary treatment concept.